A stearate-rich diet and oleate restriction directly inhibit tumor growth via the unfolded protein response - Jumpei Ogura; Koji Yamanoi; Kentaro Ishida; Eijiro Nakamura; Shinji Ito; Naoki Aoyama; Yuki Nakanishi; Toshi Menju; Kosuke Kawaguchi; Yuko Hosoe; Mana Taki; Ryusuke Murakami; et al. (Experimental and Molecular Medicine)
Abstract Fatty acids are known to have significant effects on the properties of cancer cells. Therefore, these compounds have been incorporated into therapeutic strategies. However, few studies have examined the effects of individual fatty acids and their interactions in depth. This study analyzed the effects of various fatty acids on cancer cells and revealed that stearic acid, an abundant saturated fatty acid, had a stronger inhibitory effect on cell growth than did palmitic acid, which is also an abundant saturated fatty acid, by inducing DNA damage and apoptosis through the unfolded protein response (UPR) pathway. Intriguingly, the negative effects of stearate were reduced by the presence of oleate, a different type of abundant fatty acid. We combined a stearate-rich diet with the inhibition of stearoyl-CoA desaturase-1 to explore the impact of diet on tumor growth. This intervention significantly reduced tumor growth in both ovarian cancer models and patient-derived xenografts (PDXs), including those with chemotherapy resistance, notably by increasing stearate levels while reducing oleate levels within the tumors. Conversely, the negative effects of a stearate-rich diet were mitigated by an oleate-rich diet. This study revealed that dietary stearate can directly inhibit tumor growth through mechanisms involving DNA damage and apoptosis mediated by the UPR pathway. These results suggest that dietary interventions, which increase stearic acid levels while decreasing oleic acid levels, may be promising therapeutic strategies for cancer treatment. These results could lead to the development of new cancer treatment strategies.